NANOCÓNIDOS DEL GRUPO MENDOZA (CRETÁCICO INFERIOR) EN LA PROVINCIA DEL NEUQUÉN, REPÚBLICA ARGENTINA: TAXONOMÍA, CRONOESTRATIGRAFÍA E IMPLICANCIAS PALEOGEOGRÁFICAS (Ameghiniana, 2014)
Late Jurassic–Early Cretaceous nannoconid assemblages are reported from 11 sections in the Neuquén Basin.Six species and 11 subspecies of Nannoconus Kamptner are studied systematically. Among them, Nannoconus kamptneri minor Bralower, Nannoconus kamptneri kamptneri Brönnimann, Nannoconus bucheri Brönnimann, Nannoconus circularis Deres and Achéritéguy and Nannoconus ligius Applegate and Bergen are highlighted as markers for the studied interval. Nannoconus elongatus minutus Van Niel, Nannoconus quadriangulus apertus Deflandre y Deflandre-Rigaud, Nannoconus truitti frequens Deres and Achéritéguy, Nannoconus truitti rectangularis Deres and Achéritéguy, Nannoconus truitti truitti Brönnimann are described for the first time in the Neuquén Basin. Nannoconus steinmannii minor Deres and Achéritéguy is reported for the first time inthe Southern Hemisphere. The biostratigraphic analysis suggests an ampliation of the stratigraphic ranges of Nannoconus elongatus minutus, Nannoconus quadriangulus quadriangulus Deflandre and Deflandre-Rigaud, Nannoconus quadricanalis Bown and Concheyro, Nannoconus truitti frequens and Nannoconus truitti rectangularis. Changes in the composition and diversity of the recorded nannoconid assemblages suggest variations in the paleobiogeographic and paleoecological conditions that may be helpful in the characterization of the sedimentary environments represented in the Vaca Muerta and Agrio Formations.